Reconceptualizing Education with Human Dignity: Islamic Philosophical Perspectives and Literature Insights - Triana, Devi; Ilmi, Darul; Bayu, Eka Pasca Surya (El-Rusyd, 2025)
This study examines the concept of human dignity within the context of Islamic education and explores how it is integrated into contemporary pedagogical approaches, particularly in pesantren and formal Islamic schooling systems. The research aims to identify conceptual definitions, philosophical foundations, and practical implementations of humanizing education grounded in Islamic values. A systematic literature review was conducted using the PRISMA framework, analyzing studies published between 2015–2024 sourced from Google Scholar, Scopus, SINTA, and Web of Science. Fifty-seven studies met the final eligibility criteria and were reviewed based on relevance, methodological rigor, and thematic alignment. The findings reveal three key themes: i) human dignity as a core moral and theological principle derived from Quranic anthropology and Islamic philosophical thought; ii) pedagogical frameworks that emphasize compassion, dialogical learning, learner autonomy, and ethical formation; and iii) practical implementation in classroom and pesantren contexts, showing positive effects on character development, student motivation, and ethical behavior. Despite strong conceptual grounding, gaps remain in empirical implementation evaluation and policy alignment. The study recommends further mixed-method and longitudinal research to measure the long-term impact of humanizing Islamic pedagogies. These findings contribute to strengthening ethical-based educational transformation and support Islamic education in fostering holistic, dignified, and human-centered learning environments.